2020
DOI: 10.3390/nu12082183
|View full text |Cite
|
Sign up to set email alerts
|

Maternal High Linoleic Acid Alters Placental Fatty Acid Composition

Abstract: Fetal development is modulated by maternal nutrition during pregnancy. The dietary intake of linoleic acid (LA), an essential dietary n-6 polyunsaturated fatty acid (PUFA), has increased. We previously published that increased LA consumption during pregnancy does not alter offspring or placental weight but fetal plasma fatty acid composition; the developing fetus obtains their required PUFA from the maternal circulation. However, it is unknown if increased maternal linoleic acid alters placental fatty acid sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 52 publications
1
13
0
Order By: Relevance
“…Underlying the fatty acid metabolism pathway, we identified FADS1 and ACAT2 as DEG for CAR. The FADS1 gene codes for a rate-limiting enzyme involved with the metabolism and degradation of polyunsaturated fatty acids, such as docosahexaenoic acid and arachidonic acid [ 43 ]. Likewise, the protein encoded by ACAT2 acts in lipid biosynthesis and regulates the synthesis of cholesteryl ester [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Underlying the fatty acid metabolism pathway, we identified FADS1 and ACAT2 as DEG for CAR. The FADS1 gene codes for a rate-limiting enzyme involved with the metabolism and degradation of polyunsaturated fatty acids, such as docosahexaenoic acid and arachidonic acid [ 43 ]. Likewise, the protein encoded by ACAT2 acts in lipid biosynthesis and regulates the synthesis of cholesteryl ester [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in vitro models have shown that high levels of DHA (100 µM) enhance lipid peroxidation and DNA oxidative damage in placental cells and explants [ 105 ]. On the other hand, pregnant rats fed with a LA-rich diet showed decreased placental concentrations of IL-7 and IL-10, indicating that this n -6 PUFA has both pro-inflammatory and anti-inflammatory properties in the placenta [ 106 ]. DHA seems to have beneficial effects on fetal growth but no effects on placental tissue in rat models.…”
Section: Effects Of Obesity On Fa Metabolism During Pregnancymentioning
confidence: 99%
“…An optimal long-chain n-3 fatty acid status during pregnancy is of particular benefit for cognitive and visual development of the foetus [4][5][6], and is linked to a reduction in the numbers of preterm births and low birth weights, and a reduced risk of preeclampsia and postpartum depression for the mother [1,7,8]. Furthermore, although linoleic acid (LA), omega-6 polyunsaturated fatty acid (n-6 PUFA), is an essential fatty acid, it is suggested that an adequate balance with n-3 is necessary since high levels of n-6 before or during pregnancy may have negative effects on foetal development and may influence the overall health of offspring in later stages of life [9,10].…”
Section: Introductionmentioning
confidence: 99%